USE OF DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN TEACHING RUSSIAN TO INDIAN MEDICAL STUDENTS: EXPERIENCE WITH THE INTERACTIVE PIROGOV ANATOMICAL TABLE - Atajanova A.Sh. (Uzbekistan Open Conference, 2026)
The article explores the possibilities of integrating digital technologies and elements of artificial intelligence into the process of teaching Russian to Indian medical students. It presents practical experience in using the interactive Pirogov Anatomical Table as a tool for developing professionally oriented lexical competence. The study concludes that integrating digital technologies into the traditional educational process is pedagogically justified, provided that the leading role of the teacher is maintained.
Keywords: digital technologies; artificial intelligence; professionally oriented instruction; medical terminology; interactive Pirogov Anatomical Table; Russian language; foreign students